2023
DOI: 10.15252/embr.202256074
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila mitotic spindle orientation machinery requires activation, not just localization

Abstract: The orientation of the mitotic spindle at metaphase determines the placement of the daughter cells. Spindle orientation in animals typically relies on an evolutionarily conserved biological machine comprised of at least four proteins – called Pins, Gαi, Mud, and Dynein in flies – that exerts a pulling force on astral microtubules and reels the spindle into alignment. The canonical model for spindle orientation holds that the direction of pulling is determined by asymmetric placement of this machinery at the ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Studies of HeLa and keratinocyte cells in culture have shown that LGN is required for NuMA’s cortical recruitment through metaphase, but dispensable at anaphase, where instead, 4.1 G/R serves to anchor NuMA to the cortex ( Kiyomitsu and Cheeseman, 2013 ; Seldin et al, 2013 ). Similarly, a recent study in Drosophila follicular epithelium showed that Pins is recruited apically and laterally during mitosis, while Mud is lateral ( Neville et al, 2023 ).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Studies of HeLa and keratinocyte cells in culture have shown that LGN is required for NuMA’s cortical recruitment through metaphase, but dispensable at anaphase, where instead, 4.1 G/R serves to anchor NuMA to the cortex ( Kiyomitsu and Cheeseman, 2013 ; Seldin et al, 2013 ). Similarly, a recent study in Drosophila follicular epithelium showed that Pins is recruited apically and laterally during mitosis, while Mud is lateral ( Neville et al, 2023 ).…”
Section: Discussionmentioning
confidence: 81%
“…This same study also showed that it is not the localization of Pins, but its upstream binding partner Insc, which is the best predictor of spindle orientation in Drosophila follicular epithelium, and raised the intriguing idea that there is a threshold level of Insc expression, above which it localizes apically—causing spindle misorientation—and below which it localizes laterally ( Neville et al, 2023 ). Since AGS3 can also bind Insc ( Izaki et al, 2006 ; Yuzawa et al, 2011 ), we also consider the possibility that cytoplasmic AGS3 may sequester Insc from the apical cortex in epidermal basal cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The popping out phenotype is enhanced by ectopic expression of Inscuteable, a protein that is normally expressed in neural progenitor cells (neuroblasts) in the developing nervous system (Bergstralh, Lovegrove, and St Johnston 2015; Kraut et al 1996). When it is expressed in the follicular epithelium, Inscuteable can reorient spindles so that they are parallel to the apical-basal axis, causing some daughter cells to be born outside the tissue plane (Bergstralh, Lovegrove, and St Johnston 2015; Neville et al 2023). This manipulation does not cause tissue disorganization by itself because the misplaced cells reintegrate.…”
Section: Resultsmentioning
confidence: 99%
“…The popping out phenotype is enhanced by ectopic expression of Inscuteable, a protein that is normally expressed in neural progenitor cells (neuroblasts) in the developing nervous system ( Kraut et al 1996 ; Bergstralh et al 2015 ). When it is expressed in the follicular epithelium, Inscuteable can reorient spindles so that they are parallel to the apical–basal axis, causing some daughter cells to be born outside the tissue plane ( Bergstralh et al 2015 ; Neville et al 2023 ). This manipulation does not cause tissue disorganization by itself because the misplaced cells reintegrate.…”
Section: Resultsmentioning
confidence: 99%